How Germany aims to raise standards in supply chains - Dominik Ziller (International Trade Forum, 2015)
With the advance of globalization and trade liberalization, developing countries are an ever more integral part of global supply chains. Yet the value created does not always translate into greater general prosperity in these countries, particularly the poorer ones. The cause is to be found in inadequate social standards. In many cases workers are not paid a living wage and no trade unions exist. Workers’ health and lives are at risk because of inadequate or non-existent rules governing the structural design of buildings, fire precautions or the handling of toxic chemicals. That was made dramatically clear by the Rana Plaza tragedy in Bangladesh, which claimed the lives of well over a thousand people.